Hakikat dan Tujuan Pendidikan Dalam Islam - Desi Sugihagustina; Erwinsyah Erwinsyah; Ira Wahyuningsih; Mardinal Tarigan; Marzuki Marzuki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Islamic education is education that contains at-ta'dib, at-ta'dib and talim. Education is one of the three most used words because the word has a basic meaning or meaning, namely the expression of growth, maturity, development, parenting, adaptation and support. Education is defined as an attempt to create information that is very useful. Because education covers all aspects of human life, both thoughts and feelings, knowledge. Education cannot be separated from the essence of education. As explained in previous studies, from a philosophical point of view, Islamic education is defined as a global education model, namely in the context of humanizing human liberation, creating sacred, humane and natural values ​​for the implementation of humanity as a whole. right. obligation to serve society. people . people and people People are the caliph's special devotion to the earth. This stage aims to analyze the goals of Islamic education in the world and beyond. Literature review is used as a search method. Keywords: Islamic education, essence, purpose